La exclusión residencial y el desarrollo de la ciudad moderna en América Latina: de la polarización a la fragmentación. El caso de Santiago de Chile - Rodrigo Hidalgo, D.; Axel Borsdorf, M. (Geographicalia, 2016)
At first sight, exclusive resideritial complexes with restrictive access seem to be a new phenomenon in the Latin American cities. Yet, tlie urban evolution of the countries of the region exhihit a pattern of districts separated from the rest of the urban complex in which they are entangled. During the last decades and along whith the irruption of neoliberalism ancl globalization, these living spaces covered different areas arid accommodated diverse social sectors, not only elites; increasing significanltly theirs ize, surfaces and number of inhabitans.
Keywords: gatted comunnities; urban fragmentation; urban geography